Numerical Investigation of Heat and Mass Transfer Processes while the Desorption of Hydrogen Gas Stored in MmNi4.6Fe0.4-H6 - Ali Boukhari (International Journal of Energetica)
This work presents a numerical investigation of two-dimensional coupled heat and mass transfer processes in a unit disc of an annulus-disc reactor filled with the intermetallic (Mischmetal) compound MmNi4.6Fe0.4, during the hydrogen gas desorption using the finite volume method. Temperature and amount of desorbed hydrogen and their time-averaged quantities inside the metal hydride bed are presented for different heat transfer fluid temperatures, and different metal thermal conductivities. Impacts of both effects on the metal hydride reactor performance in terms of discharging time are examined by means of a set of numerical simulations. Thus, the dehydriding time minimization relates to the adjustment of the amount of heat addition to the packed bed reactor. A good agreement was found between the present computational results and the experimental data reported in the literature.